Electrostatics and the Gating Pore of Shaker Potassium Channels - Islas, Leon D. (The Rockefeller University Press, 2001)
Various experiments have suggested that the S4 segment in voltage-dependent Na(+) and K(+) channels is in contact with a solvent-accessible cavity. We explore the consequences of the existence of such a cavity through the electrostatic effects on the gating currents of Shaker K(+) channels under conditions of reduced ionic strength S. We observe that ∼10-fold reductions of intracellular S produce reductions of the measured gating charge of ∼10%. These effects continue at even lower values of S. The reduction of gating charge when S is reduced by 10-fold at the extracellular surface is much smaller (∼2%). Shifts of the Q(V) curve because of a reduced S are small (<10 mV in size), which is consistent with very little fixed surface charge. Continuum electrostatic calculations show that the S effects on gating charge can be explained by the alteration of the local potential in an intracellular conical cavity of 20–24-Å depth and 12-Å aperture, and a smaller extracellular cavity of 3-Å depth and the same aperture. In this case, the attenuation of the membrane potential at low S leads to reduction of the apparent gating charge. We suggest that this cavity is made by a bundle of transmembrane helices, and that the gating charge movement occurs by translocation of charged residues across a thin septum of ∼3–7 Å thickness.